Patient experience in automated peritoneal dialysis with telemedicine monitoring during the COVID‐19 pandemic in Mexico: Qualitative study - Miguel Ángel Cuevas‐Budhart; Ingrid Xiomara Celaya Pineda; Diana Perez Moran; Miguel Angel Trejo Villeda; Mercedes Gomez del Pulgar; María Cristina Rodríguez Zamora; Alfonso Ramos‐Sanchez; Jose Ramón Paniagua Sierra (Wiley, 2023)
Abstract Aim The aim of the study was to understand the experiences of patients on automated peritoneal dialysis (APD) during the period of confinement due to the COVID‐19 pandemic. Design Qualitative exploratory study, phenomenological through semi‐structured telephone interview. Method A priori sampling was carried out with patients on APD with remote monitoring and telephone follow‐up, in 13 hospitals in Mexico. Results Twenty‐nine informants, mean age 45.41 ± 16.93; 15 women and 14 men. The analysis revealed four categories of analysis: home isolation, clinical follow‐up, socioeconomic challenges and infodemic. The experiences of these patients led them to somatize emotions, presenting symptoms such as anxiety, sadness, loneliness, sleep, eating and digestive disorders, situation that sets the tone for future research on telemedicine care models, coping styles, emotional support strategies and socioeconomic impact on patients with chronic home treatments during the pandemic.